2017
DOI: 10.3389/fnins.2017.00464
|View full text |Cite
|
Sign up to set email alerts
|

Brownian Optogenetic-Noise-Photostimulation on the Brain Amplifies Somatosensory-Evoked Field Potentials

Abstract: Stochastic resonance (SR) is an inherent and counter-intuitive mechanism of signal-to-noise ratio (SNR) facilitation in biological systems associated with the application of an intermediate level of noise. As a first step to investigate in detail this phenomenon in the somatosensory system, here we examined whether the direct application of noisy light on pyramidal neurons from the mouse-barrel cortex expressing a light-gated channel channelrhodopsin-2 (ChR2) can produce facilitation in somatosensory evoked fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…Our results are consistent with the idea that an inherent action of random noise is related to the observed augmentation-effects, thus in line with the previous hypothesis claiming that the stochastic resonance is an inherent property of rate-modulated random series of events (Bezrukov, 1998). Our results provide support to previous observations, claiming that the short-duration BONP on the barrel cortex of ChR2 transgenic mice can increase the evoked field potentials and the firing frequency response of pyramidal neurons to somatosensory mechanical stimulation (Huidobro et al, 2017(Huidobro et al, , 2018. Finally, to exclude an optonongenetic effect due to temperature changes induced by the delivered light (Ait Ouares et al, 2019;Ghirga et al, 2020) we examined whether our intensities of BONP up to 0.67 mW produce similar effects in wild type mice.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Our results are consistent with the idea that an inherent action of random noise is related to the observed augmentation-effects, thus in line with the previous hypothesis claiming that the stochastic resonance is an inherent property of rate-modulated random series of events (Bezrukov, 1998). Our results provide support to previous observations, claiming that the short-duration BONP on the barrel cortex of ChR2 transgenic mice can increase the evoked field potentials and the firing frequency response of pyramidal neurons to somatosensory mechanical stimulation (Huidobro et al, 2017(Huidobro et al, , 2018. Finally, to exclude an optonongenetic effect due to temperature changes induced by the delivered light (Ait Ouares et al, 2019;Ghirga et al, 2020) we examined whether our intensities of BONP up to 0.67 mW produce similar effects in wild type mice.…”
supporting
confidence: 93%
“…It means that an intermediate level of BONP can increase the peak amplitude of the Na + inward current and its inverse of latency of pyramidal neurons from the somatosensory cortex elicited by voltage-clamp microstimulation. The technique employed in the present article was based on two previous studies from our laboratory, in which we introduced a new type of brain stimulation with noisy light, termed BONP (Huidobro et al, 2017;Huidobro et al, 2018). Both studies provided support to the findings of the present article.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Recently, animal work has shown that optogenetic-noise-photostimulation of the barrel cortex in mice enhances both evoked-field and spike-firing responses to mechanical stimulation of the whiskers [ 54 , 55 ]. Optogenetic-noise-photostimulation could be used in combination with a decision task in mice [ 56 ] to further investigate the mechanism underlying our observed behavioral effect in human perceptual-decision making.…”
Section: Discussionmentioning
confidence: 99%
“…In laboratory settings, where the mechanism of action is being explored, alternative stimulation modalities such as optogenetic stimulation can be used, even at high frequencies, to examine the effects on firing rates (Deisseroth, 2015 ; Huidobro et al, 2017 , 2018 ). However, even this modality comes with its own difficulties and traps (Ayling et al, 2009 ; Cardin et al, 2009 ; Han et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%